cFOS as a biomarker of activity maturation in the hippocampal formation - Pompeiano, Maria; Colonnese, Matthew T. (Frontiers in Neuroscience, 2023)
We explored the potential for cFOS expression as a marker of functional development of “resting-state” waking activity in the extended network of hippocampus and entorhinal cortex. We examined sleeping and awake mice at (P)ostnatal-days 5, 9, 13 and 17 as well as in adulthood. We find that cFOS expression is state-dependent even at five days old, with reliable staining occurring only in the awake mice. Even during waking, cFOS expression was rare and weak at P5. The septal nuclei, entorhinal cortex layer (L)2 and anterodorsal thalamus were exceptional in that they had robust cFOS expression at P5 that was similar or greater than in adulthood. Significant P5 expression was also observed in the dentate gyrus, entorhinal cortex L6, postsubiculum L4-6, ventral subiculum, supramammillary nucleus, and posterior hypothalamic nucleus. Expression in these regions grew stronger with age and expression in new regions was added progressively at P9 and P13 by which point the overall expression pattern in many regions was qualitatively similar to the adult. Six regions - CA1, dorsal subiculum, postsubiculum L2-3, reuniens nucleus, perirhinal and postrhinal cortices were very late developing, mostly achieving adult levels only after P17. Our findings support a number of developmental principles. First, early spontaneous activity patterns induced by muscle twitches during sleep do not induce robust cFOS expression in the extended hippocampal network. Second, development of cFOS expression follows the progressive activation along the trisynaptic circuit, rather than birth-date or cellular maturation. Third, we reveal components of the egocentric head-direction and theta-rhythm circuits as the earliest cFOS active circuits in the forebrain. Our results suggest that cFOS staining may provide a reliable and sensitive biomarker for hippocampal formation activity development, particularly in regards to the attainment of a normal waking state and synchronizing rhythms such as theta and gamma.